Amplifier characteristics of darlington composite transistor - Gupta R.S. (My University, 2025)
A study has been made of the amplifier characteristics of the common collector composite transistor in which the circuits have been, analysed to obtain the expressions of current gain, voltage gain, input resistance, power gain and output resistance in terms of the various parameters of the individual transistors. Further, the expressions obtained have been simplified for similar transistors of the composite system. The variation of current gain, voltage gain, input resistance, power gain with load resistance and output resistance with source resistance has also been studied and a set of curves is given showing these variations. © 1970 Taylor and Francis Group, LLC.